Evaluation of professional soccer players` diet and body composition - Ramos, N. C.; Almeida, I. C. O.; Silva, L. L.; Jr. Sevilio, M. N. O.; Rodrigues Jr., J. F. C. (Research Quarterly for Exercise and Sport, 2025)
Background/Purpose: Soccer is considered a long-term intermittent exercise with sprints, changes of direction, accelerations and decelerations (Mohr et al., 2003). Training increases the body`s energy demand, making it necessary to develop a balanced, complete and differentiated diet for soccer players (Silva & Silva, 2023). If this does not happen, players are subject to loss of muscle mass, fatigue, decreased performance, as well as other negative impacts on their performance (Hilal et al., 2022). In addition to a proper diet, the assessment of athletes` body composition provides an important component in a physical fitness program, controlling body weight, maintaining a high level of physiological functioning, being related to health, quality of life and performance (Mantovaneli et al., 2023). Given these facts, the present study aimed to evaluate the food consumption and body composition of professional soccer players and verify the adequacy of consumption in relation to dietary recommendations.